CONCEPTUAL APPROACH TO THE PERIODIZATION OF INTERNATIONAL LAW HISTORY - Антипенко, Володимир Федорович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
A review of the collective monograph: Dmitriev A.I, Dmitriev J.A, Zadorozhnii O.V..Istoriya international law : monograph. - K .: Publishing House "Rays", 2008. - 384 p.